EXTENSION OF SEISMIC INVERSION FROM ELASTIC TO ELECTRICAL PROPERTY FOR A COMPLETE RESERVOIR CHARACTERIZATION - LIN, LEW CHEAN (2019)
The electromagnetic (EM) method provides opportunity in identifying and quantifying potential hydrocarbon reservoir although its time resolution is much lower than seismic data.